Kinetics of Sulphric Acid Curing-Roasting of Nickel Laterite for Recovering Nickel and Cobalt - Tian, Qinghua; Li, Dong; Guo, Xueyi; Shi, Wentang (Asian Journal of Chemistry, 2012)
The techniques such as X-ray fluorescence, X-ray diffraction and scanning electron microscope were used to describe the nickel laterite material's crystal structure and morphology. Nickel and cobalt were extracted from nickel laterite by sulphuric acid curing-roasting-leaching process and the kinetics of sulphuric acid curing-roasting was studied. The results show that the sulphuric acid curing of nickel and cobalt accords with the liquid-solid regional reaction model raised by Bagdasarym and the kinetic equation is expressed as ln [-ln (1-a)] = ln k + n ln t. The activation energies are determined to be 21.45 kJ/mol for nickel and 34.81 kJ/mol for cobalt, respectively which are characteristic for an internal diffusion controlled process.